Physical Exertion Monitoring: Elite Athletes Modify their Coach’s Task (Baltic Journal of Sport and Health Sciences, 2015)
Background. The objective of this study was to establish how accurately elite athletes carried out the task of a coach to perform an exercise at a given intensity. Methods. Cardiovascular indices were registered and analysed during a two-step research process. Two groups including six well-trained long-distance runners and 21 healthy non-athletes performed graded stress exercise up to the inability to continue the task. Runners took part in the second study in which heart rate and running pace were recorded during an aerobic training session. Results. Research findings showed that athletes demonstrated higher physical performance, but the maximum heart rate values achieved in the last fatigue phase did not differ significantly between the groups. No ischemic events were observed in elite athlete group during the entire physical test. Relatively stable heart rate indices in the maximal physical load step were observed in both groups, but heart rate indices were significantly lower during all physical load steps in the group of elite runners.Conclusions. Elite athletes carried out the coach’s task only in the first phase of running and further modified the task by maintaining the stability of the cardiovascular system.Keywords:  training, cardiovascular system, functional state, heart rate.